Blackcurrant (Ribes nigrum) - a true natural antioxidant - Cristina Munteanu (Amaltea Medical Publishing House, 2020)
Phytotherapy is the branch of alternative medicine that studies the treatment of various diseases with the help of plants and herbal preparations. One of the plants commonly used in phytotherapeutic treatments is blackcurrant. All its component parts are rich in active principles that are responsible for its phytotherapeutic properties. Numerous studies have approached the phytotherapeutic properties of blackcurrant. In this material we focused on researching data from the literature that include studies related to antioxidant action of blackcurrant.